2019
DOI: 10.1016/j.athoracsur.2018.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Replacement in a Patient With Dextrocardia and Situs Inversus Totalis

Abstract: This report presents the case of an 82 year old male with known dextrocardia and situs inversus totalis who developed increasing dyspnea on exertion and was diagnosed with severe aortic stenosis. Transcatheter aortic valve replacement was decided upon requiring deviation from standard techniques for patients with normal anatomy and left-sided aortic arch. We describe two technical differences required for patients with dextrocardia and right-sided aortic arch which facilitate transcatheter aortic valve replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Few cases of SIT have been reported with surgical experience at home and abroad. The case of cerebrovascular interventional surgery in SIT patients has not been reported, but there are reported cases of cardiovascular interventional surgery and open surgery ( 9 , 10 ). Matsuno et al reported the association between cerebral aneurysms and the transposition of the aorta, and the surgical clipping of the aneurysm was carried out via the right frontotemporal craniotomy on the next day after admission ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few cases of SIT have been reported with surgical experience at home and abroad. The case of cerebrovascular interventional surgery in SIT patients has not been reported, but there are reported cases of cardiovascular interventional surgery and open surgery ( 9 , 10 ). Matsuno et al reported the association between cerebral aneurysms and the transposition of the aorta, and the surgical clipping of the aneurysm was carried out via the right frontotemporal craniotomy on the next day after admission ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aortic valve (AV) abnormalities causing severe aortic regurgitation or severe stenosis may occur in dextrocardia patients [ 121 , 122 , 123 , 124 , 125 , 126 ]. Simpler balloon aortic valvuloplasty or surgical repair may be offered in younger populations.…”
Section: Management Of Cardiac Malposition Patients During Adulthoodmentioning
confidence: 99%
“…Simpler balloon aortic valvuloplasty or surgical repair may be offered in younger populations. Transcatheter [ 121 , 122 , 123 , 124 , 125 ] or surgical [ 126 ] replacement of the AV may be offered for the elderly to address AV abnormalities [ 121 , 122 , 123 , 124 , 125 , 126 ].…”
Section: Management Of Cardiac Malposition Patients During Adulthoodmentioning
confidence: 99%
“…Dextrocardia in combination with situs inversus is a rare congenital anomaly, with a frequency of 1: 10 000 [2]. Cardiac abnormalities are rare in patients with situs inversus totalis, whereas abnormalities associated with isolated dextrocardia occur more frequently.…”
Section: Introductionmentioning
confidence: 99%